Upaya Meningkatkan Hasil Belajar PAI Materi Puasa Ramadhan Melalui Pendekatan Cooperative Model STAD - Sutami Sutami Sutami (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2021)
This study aims to improve the learning outcomes of Islamic Education in Ramadhan fasting material through the cooperative approach of the STAD model in class VB SDN Gabus 01. The type of research is classroom action research. The research was conducted in three cycles. Each cycle consists of planning, implementing the action, observing, and reflecting. The research location SD Negeri Gabus 01. The subjects of the research were 27 students of class VB consisting of 14 students and 13 students. The data collection techniques are test techniques and non-test techniques which include observation, field notes, and documentation. Then the data were analyzed. The results of pre-cycle research, the percentage of completeness were only 41% with an average of 59.81, after the action had increased. In the first cycle it reached 66.67% with an average of 71.15, in the second cycle it increased to 74.08% with an average of 76.85, and the third cycle increased to 86.36% with an average of 86.29. Based on the results of the study, it was concluded that through the cooperative approach, the STAD model could improve the learning outcomes of Islamic Education in the Ramadhan fasting material for the fifth grade students of SDN Gabus 01 Pati.